NELAYAN BAJO MELAWAN HEGEMONI KAPITALIS DI KOTA DOBO, KABUPATEN KEPULAUAN ARU, PROVINSI MALUKU - Muhamad Arsat; Ansar Arifin; Munsi Lampe; Tasrifin Tahara (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
In fishing communities, there are social classes that have diametrically different interests, namely local capital owners (capitalists), boat owners (punggawa) and ship crew. This reality creates resistance between classes which is very difficult to solve. The purpose of this writing consists of two: firstly, to describe the form of capitalist hegemony over Bajo fishermen and secondly, to describe the resistance of Bajo fishermen to capitalist hegemony. This study uses a qualitative method with an ethnographic approach. This research was conducted in the Aru Islands district. The type of data consists of primary data and secondary data. Primary data collection was carried out through observation and in-depth interviews. Meanwhile, secondary data was obtained by searching literature sourcing from printed books, ebooks, online and printed journals. Management and presentation of data is done by means of data reduction, data analysis, and data presentation in a holistic-integrative manner and drawing conclusions. The results show that the fishermen group consisting of boat voters (punggawa) resisted the local capital owners (capitalists) in the form of buying other people's shipping and fishing needs and selling their catch secretly. This phenomenon is largely determined by the knowledge, feelings and suffering of fishermen as a predisposing factor to respond to and to evaluate the reality of capitalist hegemony because they have suffered too long and lived within a dehumanization frame.